ASUHAN KEPERAWATAN PADA PASIEN POST OPERASI APENDIKTOMI DENGAN MASALAH KEPERAWATAN NYERI AKUT - Hermin Lestari; Lina Ema Purwanti; Sri Andayani (Health Sciences Journal, 2023)
Appendicectomy is the surgical removal of a body part that has a problem or disease. There are two surgical methods, namely open or conventional surgery (laparotomy) or with laparoscopic techniques. Postoperative appendicectomy wounds result in the emergence of acute pain problems. The purpose of this article is to carry out Nursing Care in Postoperative Appendicectomy Patients with Acute Pain Nursing Problems including assessment, data analysis, diagnosis, intervention, implementation and nursing evaluation. Nursing care was carried out on May 30 to June 02, 2023 in Flamboyant Room II Darmayu Ponorogo Hospital for 5 days with a nursing process approach. Implementation is done with pain management. The results of the evaluation obtained the nursing problem of acute pain associated with physical trauma agents (surgical procedures) with client data showing that abdominal pain subsided on a pain scale of 1-3 and the client appeared relaxed, decreased anxiety, reduced grimacing, improved pulse frequency, increased focus, desire to eat improved, sleeping hours improved. It is hoped that this scientific paper will provide knowledge so as to prevent and reduce acute pain nursing problems in appendicectomy patients by using guided imagery techniques, advocating for increased rest, advocating self-monitoring of pain.Keywords: Nursing Care, Appendicectomy, Acute Pain